Literacy of Vocational High School Teachers Majoring in Automotive Light Vehicle Engineering The Need for Essential Skills in The Industrial Revolution 4.0 - Anwar, Choyrul; Putu Sudira (Journal of Education Technology, 2022)
Industrial revolution 4.0 changes the pattern of human life. One of the changes is the essential skills that workers must master. The automotive world is experiencing rapid development, so workers entering this field must be prepared carefully. As a transfer of knowledge and forming a reliable workforce candidate, teachers must know the essential skills that will be taught to students to face the challenges of the industrial revolution 4.0. This study aims to analyze the literacy level of SMK teachers majoring in Automotive Light Vehicle Engineering towards the essential skill needs in the Industrial Revolution 4.0 era. The research uses a quantitative approach using a survey research design. This study involved 168 SMK teachers majoring in Automotive Light Vehicle Engineering as the research sample. Collecting data using a questionnaire with a four-choice Likers scale instrument and analyzed using descriptive analysis. The results showed that the literacy level of SMK teachers majoring in Automotive Light Vehicle Engineering towards essential skill needs in the era of the industrial revolution 4.0 and included in the high category. Essential skills include digital and information skills obtaining a percentage of 75.05%, learning skills obtaining 75.33%, and life and career skills obtaining 76.13%. Although overall, in the high category, there are several items of teacher literacy on essential skills that need to be improved.